Evaluation of defoliation on tomato yield - Radin, Bernadete (2008)
To evaluate the defoliation effect on yield of tomato, two experiments were carried out in a greenhouse, in the city of Eldorado do Sul, RS, Brazil, in 2003/04 and 2004/05. Three cultivars were used in the trial. Fanny in the first year, Olympo and Empire in the subsequent year. All of them have indeterminate growth habit except by Empire which is a determinate type cultivar. Its was observed that Fanny, a cultivar taller than 2.0m achieved higher yield under increased defoliation. The Olympo having plant high lower than Fanny did not differentiate yield under the defoliation levels. The yield of cultivar Empire was negatively affected by increased defoliation. The response of the plants to defoliation depends on the cultivars, growth habit and plant height.